Adaptation and Validation of the Patient Health Questionnaire for Depression and Anxiety (PHQ-4) in a sample of Quechua-speaking Peruvians - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Cjuno, Julio; Tito-Betancur, Madona; Caycho-Rodríguez, Tomás; Vilca, Lindsey W.; Torales, Julio; Barrios, Iván (Medicina Clínica y Social, 2024)
Introduction: The Patient Health Questionnaire for Depression and Anxiety (PHQ-4) is an ultra-brief self-report measure of depression and anxiety symptoms. The PHQ-4 has not been adapted or validated in the Quechua-speaking population. Objective: This study aimed to adapt and validate the PHQ-4 in a sample of the Peruvian Quechua-speaking population with its Collao variant from Puno-Peru. Methods: A total of 221 Quechua speakers of the Collao variant (mean age 31.2 years, SD = 11.7, 47.1% male and 52.9% female) participated. Evidence of validity based on internal structure was evaluated using confirmatory factor analysis (CFA), reliability using the internal consistency method, and item difficulty and discrimination characteristics based on Item Response Theory (IRT). Results: The results indicated that all items of the PHQ-4 were relevant, consistent, and clear enough to adequately represent anxiety and depressive symptoms. The CFA results supported a one-factorial model, in which anxiety and depression items form a single latent variable with high reliability. All items of the PHQ-4 had good discrimination parameters, and the difficulty parameters indicated that the items were comparatively difficult. Therefore, a higher presence of the latent trait (anxiety and depression) is needed to answer higher response categories. Discussion: In conclusion, the PHQ-4 presented good psychometric properties as a rapid, reliable, and valid primary screening measure for Quechua speakers in need of in-depth assessment and symptom monitoring for the diagnosis and treatment of anxiety and depression.